INSPIRATION OF ISLAMIC FIGURES IN THE HISTORY OF ISLAM NUSANTARA: RASUNA SAID'S CONTRIBUTION IN BREAKING DOWN GENDER ESTABLISHMENT AND UPHOLDING HUMAN RIGHTS - Pratiwi Andriani; Bq Ratna Mulhimmah (QANUN: Journal of Islamic Laws and Studies, 2025)
This study aims to reveal: (1) the background of Rasuna Said's life, (2) Rasuna Said's contribution in fighting for women's rights in Indonesia, and (3) Rasuna Said's important role in politics, both in the pre-independence and post-independence eras of Indonesia. This study uses a historical biographical method, which emphasizes tracing the life of a figure through a historical approach. Data were collected from primary sources in the form of archives and documents, as well as secondary sources such as books, journals, and relevant articles. The findings of this study are that Rasuna Said came from a religious and educated family, who supported girls' education. She rejected colonial education and preferred religious education. Her contributions include pushing for access to education for women, fighting for equal rights in the public sphere, and her involvement in political organizations such as Sarekat Rakyat and PERMI. After independence, she became a member of the DPR and is remembered as an important symbol of women's involvement in national politics. The implications of this study indicate the importance of strengthening the narrative of women's history in the national struggle, which has so far been less exposed in depth. However, the weaknesses of this study lie in the limited primary sources available and the biographical focus that makes the study not too broad in comparing Rasuna's contributions with other female figures. This study provides a new contribution by highlighting the continuity of Rasuna Said's struggle from the pre-independence period to the independence period, as well as the integration of Islamic values ​​and nationalism in women's struggles. Another added value lies in strengthening the figure of Rasuna Said as a representation of active, progressive, and critical Muslim women in Indonesian political history.